Intraocular pressure response to corticosteroids in children. Issue 6 (June 1980) - Biedner, B Z; David, R; Grudsky, A; Sachs, U
Abstract : A total of 44 children who suffered from vernal conjunctivitis were treated with topical dexamethasone 0.1% 4 times daily for 6 weeks and tested for their intraocular pressure. There was a statistically significant difference (P less than 0.01) between the responders in our group of children and a group of normal adults reported on by Armaly in 1965.